Which green way: description of the intervention for mobilising against Aedes aegypti under difficult security conditions in southern Mexico - Arcadio Morales-Perez; Elizabeth Nava-Aguilera; José Legorreta-Soberanis; Sergio Paredes-Solís; Alejandro Balanzar-Martínez; Felipe René Serrano-de los Santos; Claudia Erika Ríos-Rivera; Jaime García-Leyva; Robert J. Ledogar; Anne Cockcroft; Neil Andersson (BMC, 2017)
Abstract Background Community mobilisation for prevention requires engagement with and buy in from those communities. In the Mexico state of Guerrero, unprecedented social violence related to the narcotics trade has eroded most community structures. A recent randomised controlled trial in 90 coastal communities achieved sufficient mobilisation to reduce conventional vector density indicators, self-reported dengue illness and serologically proved dengue virus infection. Methods The Camino Verde intervention was a participatory research protocol promoting local discussion of baseline evidence and co-design of vector control solutions. Training of facilitators emphasised community authorship rather than trying to convince communities to do specific activities. Several discussion groups in each intervention community generated a loose and evolving prevention plan. Facilitators trained brigadistas, the first wave of whom received a small monthly stipend. Increasing numbers of volunteers joined the effort without pay. All communities opted to work with schoolchildren and for house-to-house visits by brigadístas. Children joined the neighbourhood vector control movements where security conditions permitted. After 6 months, a peer evaluation involved brigadista visits between intervention communities to review and to share progress. Discussion Although most communities had no active social institutions at the outset, local action planning using survey data provided a starting point for community authorship. Well-known in their own communities, brigadistas faced little security risk compared with the facilitators who visited the communities, or with governmental programmes. We believe the training focus on evidence-based dialogue and a plural community ownership through multiple design groups were key to success under challenging security conditions. Trial registration ISRCTN27581154 .